The Leadership of School Principals in Improving Teachers' Professional Competence (Study of MTs Muhammadiyah Jayapura): Kepemimpinan Kepala Sekolah dalam Meningkatkan Kompetensi Profesional Guru (Studi MTs Muhammadiyah Jayapura) - Hasbullah, Naufal Nabil; Fahyuni, Eni Fariyatul (Indonesian Journal of Innovation Studies, 2026)
General Background: Effective school leadership drives continuous institutional development and overall educational performance within secondary education systems. Specific Background: Principals play a pivotal role in directing teacher competencies across Islamic junior high schools. Knowledge Gap: However, practical leadership execution often encounters challenges regarding teacher engagement and time constraints. Aims: This study investigates the principal leadership strategies, supporting factors, and inhibiting factors in advancing teachers' professional competence at MTs Muhammadiyah Jayapura. Results: Findings indicate that leadership strategies incorporating structured motivation, instructional supervision, and professional training successfully enhance teacher performance. Novelty: This research provides distinct empirical evidence on contextual leadership implementation within an Islamic boarding-affiliated school in Papua. Implications: Sustained leadership initiatives and optimized professional workshops systematically elevate teaching standards and long-term educational quality. Key Findings Highlights Targeted leadership strategies enhance teacher participation in continuous professional training programs. Institutional support and professional workshops strengthen pedagogical abilities and professional competencies. High teaching workloads and schedule constraints remain primary barriers to professional competence development. Keywords: Principal Leadership, Teacher Competence, Educational Quality, Professional Development, Islamic Education